2016
DOI: 10.1093/ntr/ntw139
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Tobacco Exposure Shortens Telomere Length in Children

Abstract: As reflected by telomere shortening, prenatal tobacco exposure in children can cause premature aging and increased health risks, which we suggest is entirely preventable. Not smoking during pregnancy or quitting smoking is critical to improving the health outcome of our future generations as prenatal tobacco exposure may affect children's biological programming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 50 publications
(41 reference statements)
3
25
0
1
Order By: Relevance
“…5 ) (Lee et al, 2017(Lee et al, , 2019. Cigarette smoke exposure also has an adverse effect on the telomere length in children (Ip et al, 2017). Air pollutants and cigarette smoke are common extrinsic inducers to evoke oxidative stress and inflammation in the airway Chandrasekaran et al, 2017), leading to the vulnerability of telomere (Von Zglinicki, 2002;Venkatachalam et al, 2017).…”
Section: Telomere Shorteningmentioning
confidence: 99%
“…5 ) (Lee et al, 2017(Lee et al, , 2019. Cigarette smoke exposure also has an adverse effect on the telomere length in children (Ip et al, 2017). Air pollutants and cigarette smoke are common extrinsic inducers to evoke oxidative stress and inflammation in the airway Chandrasekaran et al, 2017), leading to the vulnerability of telomere (Von Zglinicki, 2002;Venkatachalam et al, 2017).…”
Section: Telomere Shorteningmentioning
confidence: 99%
“…Ip et al examined the relationship between prenatal tobacco exposure and telomere length in children [13*]. Telomeres are the regions of repetitive nucleotide sequences at each end of a chromosome; they protect the chromosome end from deterioration or fusion with neighboring chromosomes.…”
Section: Exposure Scenariosmentioning
confidence: 99%
“…Telomeres are the regions of repetitive nucleotide sequences at each end of a chromosome; they protect the chromosome end from deterioration or fusion with neighboring chromosomes. Telomere shortening is associated with a number of adverse health outcomes including cancer, type 2 diabetes, cardiovascular diseases, Alzheimer’s disease, and early mortality [13*]. Cigarette smoking is an established cause of telomere shortening [14].…”
Section: Exposure Scenariosmentioning
confidence: 99%
“…In addition, oxidative stress also induces fetal programming which contributes to the development of adult-onset diseases (Luo, et al, 2006) Endothelial cells of blood vessels are damaged as early as during the first month of life of children exposed to second hand smoke and these effects can be detected during the first decade of life (Das, 2003). In a population representative study to investigate the association between prenatal tobacco exposure and telomere length in children (aged under 15 years with prenatal tobacco exposure), it was found that the telomere length in children with prenatal tobacco exposure was significantly shorter than in those with no exposure (mean T/S ratio = 24.9 [SD = 8.58] in exposed vs. 28.97 [14.15] in control groups; (P = 0.02) thus, leading on to premature aging and increased health risks (Ip, et al, 2016) Thus, by this imbalance between oxidants and anti-oxidants, protection afforded to the developing fetus and fetal respiratory system by the mother is compromised, causing vulnerability to oxidative DNA damage and altering the development of the respiratory system.…”
Section: Pathogenesis Of Smoke Exposurementioning
confidence: 99%